Estudio de factibilidad para la implementación de una empresa de servicios de enfermería en la ciudad de Loja, año 2023 - Flores Flores, Scarlet Monserratt (2025)
The purpose of this research was to determine the feasibility of establishing a company dedicated to the provision of nursing services in the city of Loja. Two approaches were used, exploratory and descriptive, together with techniques such as observation, surveys and samples. These methodologies allowed segmenting the population, where 381 surveys were conducted among urban families in the city of Loja, in order to identify various demands, including unsatisfied demand. The technical study details the optimal location and size of the plant, with an installed and utilized capacity of 14,087 in Injection Therapy, 13,359 in vital signs, 8,020 cannulations, 1,784 probe placement, 534 postoperative care, 1,614 elderly care, 2,293 childcare, and 243 in chronic care. In terms of the administrative and legal management of the company, the business structure and organization were established as a limited liability company (Cia. Ltda.). In the financial analysis, a total investment of ($90,743.30) U.S. dollars is revealed, with 88.98% coming from the partners ($80,743.30) and the remaining (11.02%) from an external source (bank loan in BanEcuador) ($10,000). The Net Present Value (NPV) is projected at 159.435,54, the Internal Rate of Return (IRR) is 87.07%, the Capital Recovery Period is estimated at (3) years, (8) months and (26) days, the Benefit-Cost Ratio is (0.29) cents for each dollar invested, and the Sensitivity Analysis indicates that the project can support an increase of (2.30%) in costs and a decrease of (2%) in income. In summary, based on the above, it is concluded that the implementation of the project is feasible.